2017
DOI: 10.1097/qai.0000000000001498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immediate Initiation of Antiretroviral Treatment in HIV-Positive Individuals Aged 50 Years or Older

Abstract: Background Clinical guidelines recommend immediate initiation of combined antiretroviral therapy (ART) for all HIV-positive individuals. However, those guidelines are based on trials of relatively young participants. Methods We included HIV-positive ART-naïve, AIDS-free individuals aged 50-70 years after 2004 in the HIV-CAUSAL Collaboration. We used the parametric g-formula to estimate the 5-year risk of all-cause and non-AIDS mortality under: i) immediate initiation at baseline, and initiation at CD4 count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…Indeed, ART has been reported to be more effective in developed countries where HIV patients receiving ART were shown to survive as long as the normal population do. As a result, the mean age in NARMs can be higher than that in ARMs [29, 30]. However, like a study in South Africa [31], the present study findings indicated that most NARM events were related to overdose and addiction, which occurred at the initial stages of HIV infection and lower ages.…”
Section: Discussionsupporting
confidence: 47%
“…Indeed, ART has been reported to be more effective in developed countries where HIV patients receiving ART were shown to survive as long as the normal population do. As a result, the mean age in NARMs can be higher than that in ARMs [29, 30]. However, like a study in South Africa [31], the present study findings indicated that most NARM events were related to overdose and addiction, which occurred at the initial stages of HIV infection and lower ages.…”
Section: Discussionsupporting
confidence: 47%
“…The results did not differ much between the multiply robust estimators, although the 2J multiply robust estimator was more difficult to implement compared with the J+1 multiply robust estimators. Our results were consistent with those previously published findings (Lodi et al, 2015, 2017; Wen et al, 2021), and our estimates indicate that immediate initiation of ART is at least as effective as CD4‐based initiation of ART in terms of prolonging survival.…”
Section: Discussionsupporting
confidence: 93%
“…The results did not differ much between the multiply robust estimators, although the 2 J multiply robust estimator was more difficult to implement compared with the J + 1 multiply robust estimators. Our results were consistent with those previously published findings (Lodi et al, 2015(Lodi et al, , 2017Wen et al, 2021), and our estimates indicate that immediate initiation of ART is at least as effective as CD4-based initiation of ART in terms of prolonging survival. We proposed using efficiently calibrated propensity scores in the multiply robust estimators over noncalibrated propensity scores, and showed through simulation studies that the efficiently calibrated propensity scores can improve precision when the propensity scores models are correctly specified but the outcome regression models are misspecified.…”
Section: Discussionsupporting
confidence: 93%
“…6 No surveillance data for people ageing with HIV are available from the European Centre for Disease Prevention and Control; however, published studies provide evidence of increasing numbers of prevalent cases of older people with HIV. [36][37][38][39][40] Models based on the AIDS Therapy Evaluation in the Netherlands (ATHENA) cohort predicted an increase in the median age of people with HIV on ART in the Netherlands from 43•9 years in 2010 to 56•6 years in 2030. 41 In Spain, the percentage of people with HIV engaged in clinical care impaired than were mental health aspects; the increased resilience among older people observed in some studies suggests that these individuals might have developed skills to cope with complex issues that affect their HRQOL, together with greater acceptance of illness over time and self-care.…”
Section: Number Of People Ageing With Hiv In China Europe and Latin A...mentioning
confidence: 99%